133k views
1 vote
X^2+7x+10/x-2÷x^2-25/4x-8​

User Senthil Mg
by
5.1k points

1 Answer

4 votes

Answer:


(x^2+7x+10)/(x-2)/ (x^2-25)/(4x-8)=(4x+8)/(x-5)

Explanation:

Given:

The expression to simplify is given as:


(x^2+7x+10)/(x-2)/ (x^2-25)/(4x-8)

The division of two fractions is done by replacing the division sign by multiplication sign and taking the reciprocal of the second fraction. So, the above expression becomes:


=(x^2+7x+10)/(x-2)* (4x-8)/(x^2-25)\\\\\textrm{Factoring all the given expressions, we get:}\\\\=((x+2)(x+5))/((x-2))* (4(x-2))/((x+5)(x-5))\\\\=((x+2)(x+5)4(x-2))/((x-2)(x+5)(x-5))\\\\\textrm{Cancelling like terms,we get:}\\\\=(4(x+2))/(x-5)=(4x+8)/(x-5)

Therefore, the given expression is simplified to
(4x+8)/(x-5)

User Axis
by
5.9k points